Grey Areas of Ethics: The Significance of Levinas’ Perspective on Accounting Students’ Deliberative Moral Reasoning - Kias Ayu Damara; Supriyadi Supriyadi (The Indonesian Journal of Accounting Research, 2013)
This study aims to analyze the significance of Levinas’ perspective on the deliberative moral reasoning of accounting students when facing a grey area of ethics in a corporate accounting context. In a between-subjects experimental design, 36 undergraduate accounting students at the Faculty of Economics and Business, Universitas Gadjah Mada, were randomly assigned into two groups, which are a treatment group and a control group. The first group received a treatment of Levinas’ perspective, while the second received no treatment at all. However, both responded to the same four ethical dilemmas faced by corporate accountants designed to measure their deliberative moral reasoning. As expected, students in the treatment group exhibited significantly higher deliberative moral reasoning than those in the control group. This result thus suggests that Levinas’ perspective has significance in accounting students’ deliberative moral reasoning when facing a grey area of ethics in a corporate accounting scheme.